Semantic Web Seni Pertunjukan Indonesia - Virginia, Gloria; Susanto, Budi; Proboyekti, Umi; Nugraha, Silvanus Satno (Jurusan Teknologi Informasi Universitas Semarang, 2022)
Documentation of performance arts is an effort of cultural heritage to maintain the dignity and nobility of a nation. Semantic web is a promising alternative that support the objective. From the user side, the website will be more informative, while from the technical side, the website has ontology (a well-defined formal knowledge which is highly potential to be related to other websites). This research is an effort to developed a performance arts ontology using Methontology method. To enrich the ontology, two ontologies were merged . Linked-data principal was implemented by the use of dbpedia. The ontology was evaluated based on 4 parameters (consistency, completeness, verification, and validation) and proved to be effective while implemented in a website.